Janus kinase inhibitors in immuno-inflammatory rheumatic diseases: new opportunities and prospects - E. L. Nasonov; A. M. Lila (Научно-практическая ревматология)
Despite the great success in the diagnosis and treatment of immuno-inflammatory rheumatic diseases (IIRD), which led to a significant improvement in the prognosis in many patients, the fundamental medical problems of this pathology – the restoration of quality of life and reduction of mortality to the population level – are far from solution. This served as a powerful impetus to the study of new approaches to pharmacotherapy of IIRD, one of which is associated with the use of low-molecular synthetic drugs that inhibit intracellular "signal" molecules-Janus kinase (JAK), the socalled Jakinibs. The current achievements and trends concerning the use of JAK inhibitors in the treatment of IIRD are considered.